BIOLOGIA DE ð˜ˆð˜¯ð˜¢ð˜¨ð˜¢ð˜´ð˜µð˜¢ ð˜¬ð˜¶ð˜©ð˜¯ð˜ªð˜¦ð˜ð˜ð˜¢ (ZELLER, 1879) (LEPIDOPTERA, PYRALIDAE) - Amaral Filho, B. F.; Habib, M. E. M. (REVISTA DE AGRICULTURA, 2020)
BIOLOGIA DE ð˜ˆð˜¯ð˜¢ð˜¨ð˜¢ð˜´ð˜µð˜¢ ð˜¬ð˜¶ð˜©ð˜¯ð˜ªð˜¦ð˜ð˜ð˜¢ (ZELLER, 1879) (LEPIDOPTERA, PYRALIDAE)